Interdisciplinary modeling at Shasta Lake - Saito, Laurel, author; Fontane, Darrell G., advisor; Grigg, Neil, committee member; Bartholow, John M., committee member; Johnson, Brett, committee member (Colorado State University. Libraries, 1999)
As we approach the millennium, water management is focused on ecosystem management and sustainability. These perspectives recognize the interconnectedness of ecosystems that is inherently interdisciplinary. Modeling using available scientific knowledge and theories can bridge the cultural gap between the ability to scientifically predict effects of management alternatives with certainty, and the need to make management decisions. A project is presented in which linked engineering and ecological models were employed to assess the effects of changes in reservoir operation on the Shasta Lake fishery. A recently installed temperature control device (TCD) on Shasta Dam enables reservoir managers to enhance the downstream thermal environment of endangered salmon while maximizing hydropower generation. Altered reservoir operations could affect in-reservoir fish growth through changes in thermal, nutrient and primary productivity patterns. A two-dimensional hydrodynamic model (CE-QUAL-W2) simulated water temperatures, nutrients and phytoplankton with and without the TCD operating under different hydrologic conditions. CE-QUAL-W2 water temperature predictions were input into bioenergetics models to predict fish growth through space and time. A food web-energy transfer model developed using stable isotope analysis was applied with CE-QUAL-W2 net algal production predictions to assess changes in fish growth potential. CE-QUAL-W2 predicted that, regardless of hydrologic condition, epilimnetic thermal changes were insignificant. Therefore, because fish generally reside in the epilimnion, the linked hydrodynamic and bioenergetics simulations concluded that fish would not experience substantial changes in scope for growth due to thermal effects of TCD operation. CE-QUAL-W2 predicted increased reservoir net algal production during stratification with TCD operation under hydrologically wet conditions, and the opposite during dry years. The estimated food web indicated that rainbow trout were not dependent on phytoplankton production, and therefore would not be affected by changes in net algal production. Bass were most connected to the phytoplankton food web pathways, and could experience more growth in wet years, and less growth in dry years with TCD operation. Active involvement of engineers and biologists in developing and applying the linked modeling approach at Shasta Lake provided ecosystem-level insight into reservoir management impacts. Further interdisciplinary efforts are needed to effectively address ecosystem management and sustainability of water resources.
Keywords: civil engineering; aquaculture; fish production; ecology; environmental science; aquatic sciences